Sedimenttransport und fluviale Abtragung der Jökulsá á Fjöllum im periglazialen Zentral-Island - Schunke, Ekkehard (ERDKUNDE, 1985)
This paper deals with the river Jökulsá á Fjöllum in central Iceland as the transport agent of a drainage area in nival and proglacial environments, and presents data on its suspended and dissolved load. These are based on long-term data of daily run-off and randomly taken tests of the concentration of fluvial suspended and dissolved load in the hydrological years 1963-1979. Suspended and solute load yield may be calculated by applying rating curve estimates of concentration to the observed discharge record. The average suspended sediment yield of the Jokulsa a Fjollum amounts to 1470t ·km-2 · y -1, that of the average dissolved load to 159 t ·km-2·y-1·93 percent of the total suspended sediment transport is accomplished from April till August. The total suspended load is made up of 7% base run-off, 68% glacial run-off, and 25% snowmelt run-off. The remarkably high rates of the suspended sediment and solute transport result mostly from the specific lithological character of the hyaloclastitic rocks underlying the Jokulsa catchment area, and of the sandy-silty superficial deposits, the severe erodibility of which is especially favoured by the absence of a vegetation cover. As permafrost is absent, the periglacial fluvial erosion is not affected by the thaw or cryoclastic effects of permafrost. From the geomorphological point of view, therefore, the rates of fluvial erosion - calculated by means of the suspended sediment and solute load - suffice to ascribe the deepening (5-15 m) of the periglacial stream valleys of the Jokulsa a Fjollum drainage area during the Holocene exclusively to the effects of running snowmelt water.